Revitalization of a community site-specific art and art festivals : a case of art site Naoshima - Kondo, Junko (2012)
This thesis investigates public art and art festivals in the West, and a large scale art project in Japan, Benesse Art Site Naoshima, which is yet to be defined its place in the academic world. Through the case study of Benesse Art Site Naoshima, public art, site-specific art, art festivals, and a role of art museums are discussed. There are two parts to the thesis: (1) a brief survey of public art and site-specific art (of which has roots in Land art) and, (2) the case study of Art Site Naoshima which advocates the revitalization of rural communities through arts. The central aim of this thesis is to examine a wide range of art practices which is inspired not only by the topography of a chosen site but also by the historical, social, and political background of a specific site and how the locals (the local residents and the visitors) interact and benefit from such art practice. Simply put, the focus of my research is to investigate how site-based interactive art practices which address shared social values of a specific locality, social and historical heritage of a place, and everyday scenes (customs, daily routines and habits,) would be viewed and experienced by the audience. This expanded field of art practices outside “white cube” (O’Doherty, 2007) seems to break a boundary between art objects and the audience by offering a mutual point (a site) and interactivity (physical interaction to the site). A site as the nexus of culture and life, the audience’s experience based on the interaction to site-specific artworks would be discussed and examined. In doing so, I am hoping to have a critical view on this tentative art practices which tend to engage the audience regardless of having interest in art or not.